2019
DOI: 10.1002/anie.201908021
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electrochemical Cell Microscopy Investigation of Single ZIF‐Derived Nanocomposite Particles as Electrocatalysts for Oxygen Evolution in Alkaline Media

Abstract: “Single entity” measurements are central for an improved understanding of the function of nanoparticle‐based electrocatalysts without interference arising from mass transfer limitations and local changes of educt concentration or the pH value. We report a scanning electrochemical cell microscopy (SECCM) investigation of zeolitic imidazolate framework (ZIF‐67)‐derived Co−N‐doped C composite particles with respect to the oxygen evolution reaction (OER). Surmounting the surface wetting issues as well as the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 31 publications
0
97
0
6
Order By: Relevance
“…successfully observed that the grain boundary surface terminations in gold electrodes were more active for electrochemical CO 2 reduction to CO compared to grain surfaces . In the scanning mode, SECCM can be used to map the electrochemical behavior of individual nanoparticles in a nanoparticle ensemble thereby enabling subtle peculiarities other than nanoparticle size such as orientation, exposed facets, effect of particle agglomeration, and support–nanoparticle interactions, among others, to be resolved …”
Section: Activity Stability and Selectivitymentioning
confidence: 99%
“…successfully observed that the grain boundary surface terminations in gold electrodes were more active for electrochemical CO 2 reduction to CO compared to grain surfaces . In the scanning mode, SECCM can be used to map the electrochemical behavior of individual nanoparticles in a nanoparticle ensemble thereby enabling subtle peculiarities other than nanoparticle size such as orientation, exposed facets, effect of particle agglomeration, and support–nanoparticle interactions, among others, to be resolved …”
Section: Activity Stability and Selectivitymentioning
confidence: 99%
“…beobachtet, dass die Korngrenzen in Goldelektroden aktiver für die elektrochemische CO 2 ‐Reduktion zu CO sind als Kornoberflächen . Im Rastermodus kann SECCM verwendet werden, um das elektrochemische Verhalten einzelner Nanopartikel in einem Nanopartikelensemble abzubilden, wodurch weitere Einflussgrößen außer der Nanopartikelgröße wie Orientierung, freiliegende Facetten, Effekte von Nanopartikel‐Agglomeration und Träger‐Nanopartikel‐Interaktionen aufgelöst werden können …”
Section: Aktivität Stabilität Und Selektivitätunclassified
“…Die meisten Studien wurden aufgrund der günstigen Benetzungseigenschaften in saurem Elektrolyt durchgeführt. Kürzlich wurden unter Verwendung einer löslichen, reversiblen Redoxspezies – eines N 6 ‐koordinierten Os‐Komplexes – als interner Standard zusammen mit einem rigorosen Messregime TOF‐Werte im Bereich von 0.25 bis 1.5 s −1 pro Co‐Atom im Potentialbereich von 1.70 bis 1.80 V (gegen RHE) für einzelne von ZIF‐67‐MOF abgeleitete Co‐C‐Partikel für die OER bestimmt . SECCM hat sich daher als robustes Hilfsmittel für die direkte Visualisierung und quantitative Untersuchung von Oberflächen mit nanoskaligen Abmessungen und einzelnen Nanopartikeln zur Auflösung der zusammensetzungs‐ und morphologieabhängigen elektrokatalytischen Aktivität durchgesetzt.…”
Section: Aktivität Stabilität Und Selektivitätunclassified
“…Currently, tailoring the composition of transition metal-based compounds (such as incorporating heteroatoms or foreign metal atoms into the lattice) and constructing high-speed diffusion channels are widely deemed as effective strategies to design electrocatalysts. [10][11][12][13][14][15] For example, Yuan et. al suggested a facile supersaturated co-precipitation method to synthesize amorphous NiFeMo oxides with uniform distribution of elements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the individual active centers and insufficient transfer efficiency hinder their practical application. Currently, tailoring the composition of transition metal‐based compounds (such as incorporating heteroatoms or foreign metal atoms into the lattice) and constructing high‐speed diffusion channels are widely deemed as effective strategies to design electrocatalysts . For example, Yuan et.…”
Section: Introductionmentioning
confidence: 99%